Evaluation of transmission conditions for thin reactive heat-conducting interphases - Mishuris, Gennady S. (Scitec Publications Ltd., 2008)
Imperfect transmission conditions modelling a thin reactive intermediate layer between two bonded materials in a dissimilar strip are derived in this paper. The interphase material is assumed to be heat-resistant and situated in a thin rectangular domain between the main materials. Different types of the interphase are investigated in detail: constant and temperature dependent sources.